2018
DOI: 10.15544/jws.2018.001
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Aquatic Macrophytes Eichhornia Crassipes, Pistia Stratiotes and Salvinia Molesta in Phytoremediation Of Textile Wastewater

Abstract: Phytoremediation is an emerging low cost green technology, which uses plants for treating contaminant in the environment. Phytoremediation potential of locally available aquatic plants Eichhornia crassipes (water hyacinth), Pistia stratiotes (water lettuce) and Salvinia molesta (water fern) in the treatment process of textile wastewater was investi-gated. The reduction efficiencies of chemical oxygen demand (COD), total solids (TS), total suspended solids (TSS), total dissolved solids (TDS), nitrates, phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
5
18
1
Order By: Relevance
“…The increase in nitrate concentration observed in the L. minor effluent samples maybe due to the action of duckweed pests that fed on the L. minor plants prior to the final day of the sampling period. The results obtained in the P. stratiotes treatment system corroborates with the findings of Wickramasinghe and Jayawardana (2018). This study demonstrated that P. stratiotes plants exhibited high efficiency in nitrate uptake than L. minor plants.…”
Section: Determination Of Nitrate Concentrationsupporting
confidence: 88%
“…The increase in nitrate concentration observed in the L. minor effluent samples maybe due to the action of duckweed pests that fed on the L. minor plants prior to the final day of the sampling period. The results obtained in the P. stratiotes treatment system corroborates with the findings of Wickramasinghe and Jayawardana (2018). This study demonstrated that P. stratiotes plants exhibited high efficiency in nitrate uptake than L. minor plants.…”
Section: Determination Of Nitrate Concentrationsupporting
confidence: 88%
“…However, the increased acidity level of pH recorded in the L. Minor treated wastewater sample in this study was higher than the findings reported by [23]. Meanwhile, the percentage reduction values of pH concentration in P. Stratiotes and E. Crassipes treated wastewater samples were lower than the pH reduction level of 50-75% achieved in the study carried out by [24], but higher than the slight reduction level of pH achieved by [25] in their study of the phytoremediation of landfill leachate waste contaminants using P. Stratiotes and E. Crassipes. The pH reduction observed in the P. Stratiotes treated wastewater sample correlate with the findings of [26] that P. Stratiotes reduced alkaline pH concentration to neutral.…”
Section: B Mean Concentration Of Ph At Different Treatment Intervalscontrasting
confidence: 86%
“…Various types of industries are located in India viz., textile, tannery, pharma, glass making company, sugar manufacturing, paper-making company, etc. Currently, most of the industries are facing a major problem for the treatment of wastewater and need environment-friendly technologies for the management of wastewater, which could be helpful to create an ecofriendly environment Wickramasinghe & Jayawardana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of green plants to remediate water pollution provides a sustainable, solar-driven, costeffective, less harmful, and eco-friendly process; therefore, it is gaining more attention of scientific community (Ismail et al, 2015;Kumar & Chopra, 2018). Water lettuce (Pistia stratiotes L.) belonging Araceae family has a high potential of absorbing pollutants and other toxic heavy metals from, also a high mark of cellular multiplication (Wickramasinghe & Jayawardana, 2018). Due to this, it can grow under stressed conditions and also accumulates various pollutants within its vegetative parts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation